Analisis Dampak Penerapan Program Lubang Cerdas Organik (LCO) Terhadap Efektivitas Pengurangan Sampah Organik Di Desa Lamajang RW 19 - Susi Maulinawati; Rahma Nur Naila; Andi Zan Jaya; Muhammad Rusdi; Nita Amalia; Reva Nur Labibah; Salis Afriliana; Vivia Alifah; Riyadh Fadil; Sanju Satria Nugraha; Rifky Nabil Falah; Jefry Nur Yasin (Universitas Insan Cendekia Mandiri, 2026)
Organic waste is a biodegradable material, but it can cause environmental problems at the household and community level, especially if it accumulates due to an inefficient management system. The Smart Organic Hole (LCO) Program is an initiative for managing household organic waste in the Thematic-based Real Work Lecture (KKNT) Group 3 in Lamajang Village, Cibolang Village RW 19. This alternative technology is a simple method that allows for the processing of organic waste directly in the soil as the initial process of compost formation. Based on the culture and awareness of the community towards environmental concerns, this program is easy to implement by the community by starting with intensive education. This program aims to reduce the accumulation of organic waste in the environment by processing it into natural compost through infiltration holes made in strategic locations, then evaluating its effectiveness in reducing organic waste generation, and assessing its impact on community behavior and environmental conditions. Program implementation includes three main stages: (1) Preparation which includes location surveys and socialization; (2) Implementation which includes digging holes and training in filling organic waste; (3) Monitoring and evaluation which includes monitoring the compost decomposition and harvesting process. The research approach used a quasi-experimental method through the implementation of LCO at the KKNT location with a one-month implementation duration. Observed parameters included the reduction in household organic waste generation, the volume of degraded organic material in the initial phase, and community response and participation. Socialization and training were conducted for 20 heads of families (KK) as a pilot project out of a total of 147 KK. Two LCO units were installed as a medium for decomposing organic waste, with filling carried out in stages. Monitoring showed active community participation and the potential for reducing organic waste by ±2–3% of the total waste generation in RW 19 during the program period. Although the use of compost fertilizer could not be implemented due to the limited duration of the KKN, this program demonstrated the initial effectiveness of LCO and the potential for sustainability if implemented gradually to all residents. Suggestions were given for expanding its implementation, conducting routine monitoring, and providing maintenance guidelines to achieve a more significant impact on organic waste reduction. Organic waste is a biodegradable material, but it can cause environmental problems at the household and community level, especially if it accumulates due to an inefficient management system. The Smart Organic Hole (LCO) Program is an initiative for managing household organic waste in the Thematic-based Real Work Lecture (KKNT) Group 3 in Lamajang Village, Cibolang Village RW 19. This alternative technology is a simple method that allows for the processing of organic waste directly in the soil as the initial process of compost formation. Based on the culture and awareness of the community towards environmental concerns, this program is easy to implement by the community by starting with intensive education. This program aims to reduce the accumulation of organic waste in the environment by processing it into natural compost through infiltration holes made in strategic locations, then evaluating its effectiveness in reducing organic waste generation, and assessing its impact on community behavior and environmental conditions. Program implementation includes three main stages: (1) Preparation which includes location surveys and socialization; (2) Implementation which includes digging holes and training in filling organic waste; (3) Monitoring and evaluation which includes monitoring the compost decomposition and harvesting process. The research approach used a quasi-experimental method through the implementation of LCO at the KKNT location with a one-month implementation duration. Observed parameters included the reduction in household organic waste generation, the volume of degraded organic material in the initial phase, and community response and participation. Socialization and training were conducted for 20 heads of families (KK) as a pilot project out of a total of 147 KK. Two LCO units were installed as a medium for decomposing organic waste, with filling carried out in stages. Monitoring showed active community participation and the potential for reducing organic waste by ±2–3% of the total waste generation in RW 19 during the program period. Although the use of compost fertilizer could not be implemented due to the limited duration of the KKN, this program demonstrated the initial effectiveness of LCO and the potential for sustainability if implemented gradually to all residents. Suggestions were given for expanding its implementation, conducting routine monitoring, and providing maintenance guidelines to achieve a more significant impact on organic waste reduction. Organic waste is a biodegradable material, but it can cause environmental problems at the household and community level, especially if it accumulates due to an inefficient management system. The Smart Organic Hole (LCO) Program is an initiative for managing household organic waste in the Thematic-based Real Work Lecture (KKNT) Group 3 in Lamajang Village, Cibolang Village RW 19. This alternative technology is a simple method that allows for the processing of organic waste directly in the soil as the initial process of compost formation. Based on the culture and awareness of the community towards environmental concerns, this program is easy to implement by the community by starting with intensive education. This program aims to reduce the accumulation of organic waste in the environment by processing it into natural compost through infiltration holes made in strategic locations, then evaluating its effectiveness in reducing organic waste generation, and assessing its impact on community behavior and environmental conditions. Program implementation includes three main stages: (1) Preparation which includes location surveys and socialization; (2) Implementation which includes digging holes and training in filling organic waste; (3) Monitoring and evaluation which includes monitoring the compost decomposition and harvesting process. The research approach used a quasi-experimental method through the implementation of LCO at the KKNT location with a one-month implementation duration. Observed parameters included the reduction in household organic waste generation, the volume of degraded organic material in the initial phase, and community response and participation. Socialization and training were conducted for 20 heads of families (KK) as a pilot project out of a total of 147 KK. Two LCO units were installed as a medium for decomposing organic waste, with filling carried out in stages. Monitoring showed active community participation and the potential for reducing organic waste by ±2–3% of the total waste generation in RW 19 during the program period. Although the use of compost fertilizer could not be implemented due to the limited duration of the KKN, this program demonstrated the initial effectiveness of LCO and the potential for sustainability if implemented gradually to all residents. Suggestions were given for expanding its implementation, conducting routine monitoring, and providing maintenance guidelines to achieve a more significant impact on organic waste reduction. Thus, the LCO program is considered effective as an initial strategy for reducing organic waste and means of environmental education, although the production of mature compost requires a longer processing time